(untitled) (Jurnal Riset Manajemen Akuntansi Indonesia, 2023)
The subjects in this study were 3 employees of the PPKB PPPA Social Service in Magelang Regency, namely 1 Head of Women Empowerment and Child Protection, 1 Head of Women Empowerment Section, and 1 PPKB PPPA Social Service in Magelang Regency. Data analysis in this study refers to the thinking or theory of Miles and Huberman (1992) which includes 3 (three) steps of activity after the process of data collection and drawing conclusions.As a result, the improvement in handling cases of violence against women in Magelang Regency has been carried out based on performance indicators of productivity, service quality, responsiveness, responsibility, but the performance of handling cases of violence against women is still less than optimal, this is due to (1) Lack of employees to handle women protection affairs. (2) Lack of operational funds for women and children protection programs and for cadre training. (3) Lack of facilities and infrastructure, (4) Protection of women and children victims of violence is a network with other institutions. In order to obtain data from the prosecutor office, it is sometimes difficult to obtain data about the victim. Efforts to improve the handling of cases of violence against women at the PPKB PPPA Social Service in Magelang Regency, namely: (1) Adding employees with psychological backgrounds to handle women protection affairs, especially in providing counseling or psychological assistance to women victims of violence. (2) Manage operational funds for women and children protection programs and for the training of trained cadres for handling existing victims of violence, both women and girls. (3) Addition of facilities and infrastructure, such as shelters for women victims of violence, shelter houses in collaboration with other non-governmental organizations, as well as means of program socialization through radio, webside and online media in the form of Instagram, Facebook, etc.. (4) Increasing cooperation with networks in an effort to improve services for handling and protecting women victims of violence.